Tobacco Smoking and Alcohol Drinking among Youth in Duhok, Iraq: A Cross-sectional Study - Bakhtiyar Ahmed Rasheed Baba Hajee; Saad Younis Agha (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Tobacco smoking and alcohol drinking are among the high risk health behaviours that determine individual and community health, increasing risk of chronic diseases like cardiovascular diseases and cancer, and of early mortality. Aim: To determine the prevalence and pattern of tobacco and alcohol use among youths in Duhok Province, Kurdistan Region of Iraq. Materials and Methods: This community based cross-sectional study conducted from September 2020-January 2021 in Duhok Province, Iraq. Systematic random sampling was used to interview 729 youths (15-24 years) (366 males and 363 females), who visited the Premarital Screening and Counselling Health Clinic in Duhok city, Iraq. Data collection was done using questionnaire based on the World Health Organisation (WHO) STEPwise approach to Non Communicable Diseases (NCD) surveillance. Data were analysed by Statistical Package for the Social Sciences (SPSS) version 26.0, and association between variables was calculated using the Chi-squared test and logistic regression. Results: Prevalence of tobacco smoking among youth was 20.3%, (25.4% in males and 15.2% in females). Males were 2.2 times more likely to smoke tobacco (OR: 2.2). Nargila/waterpipes was the most commonly used tobacco product (19.5%) followed by cigarettes (14.1%). Prevalence of alcohol drinking was 4.0%, (7.1% in males and 0.8% in females). Conclusion: Tobacco smoking among youth in Duhok was high, especially among females, with more use of Nargila/waterpipes. Exposure to second hand smoking was very high. Alcohol drinking was higher than WHO estimate for Iraq.